Dental transposition: characterization and dental anomalies associated with a population of Cali, Colombia, 1997-2011 - Hernández, Jesús A.; Villavicencio, Judy; Arango, María Cristina (Revista Facultad de Odontología Universidad de Antioquia, 2013)
Introduction: the purpose of this study was to characterize dental transposition in a population consulting a pediatric dental service in Cali, Colombia, between January 1997 and October 2011 and to describe associated dental anomalies. Methods: this was a retrospective descriptive study. A total of 1809 panoramic radiographs were reviewed in order to establish the presence of dental transposition and associated dental anomalies. The following variables were recorded: age at diagnosis; gender; family, medical, and stomatognathic histories; trauma to the primary and permanent dentition; location and presence of other associated dental anomalies. Results: out of the 1809 patients reviewed, four had dental transposition (0.22%), all of them females. The age range was 7-15 years. No relevant family, medical or stomatognathic histories were found. Three of the cases occurred in the maxilla and one in the mandible. There was no side predominance for the transpositions. One of the mandible cases was bilateral and the other two were unilateral. The associated dental anomaly usually found was persistent temporary canines in all the cases. Conclusions: this study found a prevalence of dental transposition of 0.22% (4 cases in 1809 patients); all of the cases occurred in female patients and 75% of them were located in the upper maxilla.